Differential dependence on nuclear factor-κB-inducing kinase among natural killer T-cell subsets in their development - Noma, Haruka (Immunology, 2015)
Natural killer T cells (NKT cells) are comprised of several subsets. However, the possible differences in their developmental mechanisms have not been fully investigated. To evaluate the dependence of some NKT subpopulations on nuclear factor-κB-inducing kinase (NIK) for their generation, we analysed the differentiation of NKT cells, dividing them into subsets in various tissues of alymphoplasia (aly/aly), a mutant mouse strain that lacks functional NIK. The results indicated that the efficient differentiation of both invariant NKT (iNKT) and non-iNKT cells relied on NIK expression in non-haematopoietic cells; however, the dependence of non-iNKT cells was lower than that of iNKT cells. Especially, the differentiation of CD8(+) non-iNKT cells was markedly resistant to the aly mutation. The proportion of two other NKT cell subsets, NK1.1(+) γδ T cells and NK1.1(−) iNKT cells, was also significantly reduced in aly/aly mice, and this defect in their development was reversed in wild-type host mice given aly/aly bone marrow cells. In exerting effector functions, NIK in NKT-αβ cells appeared dispensable, as NIK-deficient NKT-αβ cells could secrete interleukin-4 or interferon-γ and exhibit cytolytic activity at a level comparable to that of aly/+ NKT-αβ cells. Collectively, these results imply that the NIK in thymic stroma may be critically involved in the differentiation of most NKT cell subsets (although the level of NIK dependence may vary among the subsets), and also that NIK in NKT-αβ cells may be dispensable for their effector function.